2018
DOI: 10.21061/jvs.v3i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Students Veterans’ Preference for Traditional Versus Online Course Formats: A Case Study at Two Midwestern Universities

Abstract: Recently, there have been many discussions about how to meet student veterans' needs according to curricular and course formats. While national studies indicate that many student veterans enroll in online classes, questions about the nature of their preferences and requisites, especially in some university environments, remain. For instance, how do on-ground and online course formats address different student veterans' needs and desires? This article discusses a three-year, case study of student veterans' cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Of these models, which can be seen as fluid, instructors could opt to offer military-related readings to students in any format. 8 Specific to the third model, a "service-member/veteran-focused course" cohort design (see Hart & Thompson, 2016), Hembrough founded a Composition II course with a service-member/veteran cohort in which students read and wrote about military-themed subjects (Hembrough & Dunn, 2019), and veteran-friendly and service-member/veteran-focused cohort courses can attract both service-members/veterans and other students, including military spouses and war survivors. The literature describes obstacles to all three course models' implementation, namely facilitating debates about the term "veteran" that disturb a classroom's student demographic (Hart & Thompson, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these models, which can be seen as fluid, instructors could opt to offer military-related readings to students in any format. 8 Specific to the third model, a "service-member/veteran-focused course" cohort design (see Hart & Thompson, 2016), Hembrough founded a Composition II course with a service-member/veteran cohort in which students read and wrote about military-themed subjects (Hembrough & Dunn, 2019), and veteran-friendly and service-member/veteran-focused cohort courses can attract both service-members/veterans and other students, including military spouses and war survivors. The literature describes obstacles to all three course models' implementation, namely facilitating debates about the term "veteran" that disturb a classroom's student demographic (Hart & Thompson, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, one nonveteran student surveyed found some material we studied to be too "graphic" and "depressing," even though she did not want alternative readings. Whether or not students enjoyed reading about military topics, all found it useful to discuss the definitions of a "veteran" that the readings raised, as well as stereotypes that society utilized to describe veterans (see Hembrough & Dunn, 2019). In a recent national survey, most participants reported having "only respect" for veterans by ranking their social merit on par with firefighters and even above that of teachers and police officers (Jordan, 2019).…”
Section: Reading Military-themed Work Related To Students' Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…While studies indicate that many student service-members/veterans prefer online courses to accommodate their work and family obligations (ACE, 2014), the service-members/veterans surveyed indicated a preference for brick-and-mortar courses, especially if they provided opportunities to interact with other service-members/veterans in person and to discuss their military backgrounds (see Hembrough, Madewell, & Dunn, 2018). Comparably, compositionist and veteran, Angie Mallory (2016), who created a FYC veteran cohort at Iowa State University, liked the easy, military "banter" her students introduced into discussions.…”
Section: Establishing a Military-friendly Cohort For The Service-membmentioning
confidence: 99%
“…While online courses offer time management and location flexibility to students, the unstructured environment and lack of traditional face-to-face accountability that characterizes online courses may not always benefit student veterans (Klingsieck, Fries, Horz, & Hofer, 2012;Goda et al, 2015). One study found that student veterans preferred in-seat classes to online courses, reporting that the inseat format gave them a better connection with their instructors and classmates (Hembrough, Madewell, & Dunn, 2018). No studies have been conducted regarding student veterans' preferences for studying nursing in online, hybrid, or face-to-face settings.…”
Section: Review Of Literaturementioning
confidence: 99%